Mapping the Distribution of Pulmonary TB Cases Using ArcView GIS 3.3 in the Working Area of ​​Penurunan Community Health Center, Bengkulu City - Ismail Arifin; Nofri Heltiani (ANJANI Journal (Medical Science & Healthcare Studies), 2026)
Problem: Tuberculosis (TB) remains one of the top ten causes of death worldwide. Bengkulu City, particularly the service area of Penurunan Public Health Center, has experienced an increase in pulmonary TB cases over the past two years. The lack of spatial-based data hinders the identification of priority intervention areas. Objective: The spatial distribution of pulmonary TB cases based on age, gender, and location in the working area of Penurunan Health Center using ArcView GIS 3.3. Methods: This study employed a descriptive quantitative design with a spatial analysis approach. Secondary data were obtained from medical records for 2023–2024 and analyzed using univariate methods. The sample included all pulmonary tuberculosis (TB) cases from four villages in the working area of Penurunan Public Health Center. Result: The number of cases increased from 10 (2023) to 23 (2024). Most cases occurred in males (60.6%) and in the 25–34 and ≥45 year age groups. The highest case concentrations were found in Penurunan and Belakang Pondok villages. The priority map identified Penurunan as a very high-priority area. Recommendation: Routine mapping by the health center and the development of an integrated spatial system by the City Health Office are recommended. Future research should cover a wider geographical scope and utilize more modern GIS software